Recovery heart rate in dynamic and statics sports - Beltran Contreras, S.; Peinado, A. B.; Butragueno, J.; Rojo-Tirado, M. A.; Benito, P. J.; Calderón, F. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: The fall in heart rate (HR) immediately after dynamic exercise has been studied by some authors [1, 2]. This decrease is considered to be a function of the reactivation of the parasympathetic nervous system [1]. The aim of this study was to compare the rate of recovery of the HR in several sports classified as statics (S) and dynamics (D). Methods: 294 Spanish athletes of international level, from statics (n=89) and dynamics (n=205) sports, were evaluated. Each subject performed an incremental test until exhaustion in treadmill or cicloergometer. The expired air was analyzed with a gas analyzer. The response of heart rate (HR) during the first 4 minutes of a passive recovery after maximum effort was analyzed. Recovery rate index (IR) was calculated using the equation proposed by Calderon (IR1) [3]. A Student`s unpaired t test was used to compare the HR recovery and IR between S and D sports. The significance level was set at 0.05. Results: The maximum HR was not different between groups (p>0.05) (D: 195.6±9.9 beats•min-1 vs. E: 194.7±10.4 beats•min-1). However, the basal HR in S group was higher than D sports (p<0.05) (60.5±11.6 beats•min-1 vs. 57.2±9.4 beats•min-1, respectively). The HR recovery in minute 4 during the passive recovery was not significantly higher in S (120±14.2 beats•min-1) than in D (117±14.6 beats•min-1). IR1 was not significantly higher in D (IR1 min4: 56.8±8.6 %) than in S sports (min4: 55.4±7.4 %). Discussion: The recovery of HR in S and D sports was similar, showing that the type of training does not influence the rate of recovery of the HR [3]. The cardiac parasympathetic reactivation is the principal determinant of the immediate fall in HR when exercise ceases [1], and this mechanism seems to function independently of the type of training. Indeed, we believe that use the IR proposed is more useful to study the HR recovery, since takes into account the HR reserve.